100 Powerform for real-time entry of routine cardiac outpatient data into the electronic health record: application for audit and research. (5th June 2017) - Bodagh, Neil; Archbold, Andrew; Weerackody, Roshan; Barnes, Mike; Robson, John; Timmis, Adam
Abstract : Background: The electronic health record (EHR) is the major repository of clinical data in the NHS. It is a huge potential resource but remains severely under-utilised to the point that almost none of the UK's audit and research output is based on routinely collected clinical data. The reasons are complex but ultimately reflect the fact that these data are rarely entered into the EHR in a form that allows for their organised storage and digital download. Methods: We have developed a SNOMED-based electronic powerform comprising a user-friendly interface for real-time entry of clinical data into the hospital EHR during cardiac outpatient consultation. Our aim was to capture outpatient clinical data in a form that allows for automatic development of summary patient reports and for batch download of de-identified data for audit and research. Results: During the first 4 months after installation of the powerform, consultant utilisation averaged 60% for the 327 new patients seen during that period. Presenting symptoms, examination findings, investigations, diagnosis, initial treatment and disposal (>120 fields) were entered in real time during consultation and a structured summary report was developed. This was made available for electronic transfer directly into the patients EMIS file in the primary care record, permitting same-day delivery of the report and obviating the need for a dictated clinic letter. Batched download of the digital data was successful, with sample analytic findings as follows: Patient ethnicity: South Asian 44%, white 34%, black 15% Presenting symptom: Chest pain 41%, dyspnoea 11%, palpitations 10%, dizzy attacks/syncope 8%, hypertension 7% Diagnosis: Non-cardiac chest pain 24%, angina 11%, coronary disease 7% Disposal: discharged to GP 74%, follow-up appointment 11%, cath lab waiting list 6%, referral to specialist clinic 9%. Ongoing are surveys of satisfaction with the power forms (cardiologists) and with the summary reports (GPs). Conclusion: This is the first report of powerform development for entry of routinely collected cardiac outpatient data into the hospital EHR. The data are stored in a form that permits: (1) automatic generation of a summary report for same-day delivery into the primary care record and (2) batch download of de-identified digital data for audit. Integration of the system with programmes of generic patient consent will open up the EHR to real-world clinical research.